780. Incidence and Prevalence of Nontuberculous Mycobacterial Lung Disease in US Medicare, 2008–2015. (26th November 2018) - Winthrop, Kevin L; Adjemian, Jennifer; Mirsaeidi, Mehdi; Marras, Theodore; Eagle, Gina; Zhang, Raymond; Wang, Ping; Chou, Engels; Zhang, Quanwu
Abstract: Background: Previous research has reported nontuberculous mycobacterial lung disease (NTMLD) prevalence of 47 per 100, 000 among Medicare beneficiaries ≥65 years in 2007, with an average increase of 8.2% annually between 1997 and 2007. In this study, we have evaluated NTMLD incidence and prevalence in Medicare between 2008 and 2015. Methods: Patients diagnosed for NTMLD with an ICD9 031.0 were identified from the Medicare database (N≈30 million yearly), not including the Part C portion. Individuals who incurred at least 2 medical claims ≥30 days apart between 2007 and 2015 were considered as a positive NTMLD case, yielding 58, 294 patients. All individuals fulfilling the case definition each calendar year were considered as prevalent cases. Incident cases included those meeting case criteria and who did not have a Medicare claim for NTMLD in the prior year. Poisson regression was used to estimate yearly confidence intervals. ARIMA models were used to forecast incidence and prevalence over 2016–2025. Results: Patients with NTMLD in the Medicare database had a mean age of 74 (standard deviation: ±10) years. Sixty-nine percent were women and 89% white. Yearly NTMLD incidence increased from 20.7 (95% CI: 20.2–21.3) in 2008 to 28.1 (27.5–28.7) in 2013 per 100, 000 Medicare beneficiaries and leveled to 27.6 (26.9–28.2) in 2014 and 25.9 (25.3–26.5) in 2015 per 100, 000. Yearly NTMLD prevalence increased throughout the observation period from 41.6 (40.9–42.3) in 2008 to 63.1 (62.2–64.0) in 2015 per 100, 000 Medicare beneficiaries. Incidence was 28.1 vs. 14.7 per 100, 000 in 2015 in Medicare beneficiaries ≥65 years vs. those <65 years, respectively. Prevalence was 70.2 vs. 27.9 per 100, 000 in 2015 in Medicare beneficiaries ≥65 years vs. those <65 years, respectively. In 2015, incidence and prevalence were higher in women than men (33.9 vs. 16.0/100, 000 and 86.2 vs. 34.6/100, 000, respectively) and among individuals of Asian origin compared with White (41.1 vs. 27.6/100, 000 and 89.4 vs. 68.7/100, 000, respectively). The 10-year incidence and prevalence forecasts were presented in figures. Conclusion: In US Medicare beneficiaries, NTMLD incidence increased from 2008 through 2013 and leveled off in more recent years, while NTMLD prevalence continued to rise through 2015. Disclosures: K. L. Winthrop, Insmed Incorporated: Scientific Advisor, Consulting fee and Research grant. T. Marras, Insmed Incorporated: Investigator, Consulting fee and Research grant, Horizon Pharmaceuticals: Consultant, Consulting fee, Red Hill: Consultant, Consulting fee, AstraZeneca: CME, Speaker honorarium. G. Eagle, Insmed Incorporated: Employee, Salary. R. Zhang, Insmed Incorporated: Consultant, Consulting fee. P. Wang, Insmed Incorporated: Employee, Salary. E. Chou, Insmed Incorporated: Employee, Salary. Q. Zhang, Insmed Incorporated: Employee, Salary.